Methanolic Extract From Cocoa Bean (Theobroma Cacao L.) As A Potential Active Ingredient In Mouthwash - Ainun Mardiah; Cut Aja Nuraskin (Institute of Computer Science (IOCS), 2022)
Dental plaque is a soft deposit firmly attached to the surface of teeth, formed from a mixture of saliva; such as mucin, remnants of oral tissue cells, leukocytes, lymphocytes with food debris, and bacteria resulting in the initial occurrence of tooth decay due to reduced pH. Unfortunately, currently available antiseptics-based mouthwash, used to prevent dental plaque formation, is thought to have a carcinogenic effect. Therefore, an alternative plaque was proposed using herbal antibacterial agents. Cocoa beans have anti-bacterial properties and are known to have active anti-bacterial agents, these substances are flavonoids, phenolics, alkaloids, terpenoids, saponins, and tannins. Herein, we aimed to determine the phytochemical content of methanol extract from cocoa bean (Theobroma cacao L.) and its antibacterial activities against Streptococcus mutans and subsequently studied its potential as a mouthwash active ingredient. Macerated methanolic extract of cocoa bean was investigated against clinical isolates of S. mutans. Qualitative phytochemical tests were further performed to observe the presence of flavonoids, phenolics, alkaloids, terpenoids, saponins, and tannins. The results showed that the growth of S. mutans colonies at a concentration of 1, 2, and 3% were 431×104, 142×104, and 59.5×104 CFU/mL, respectively. Addition of the extract at all concentrations (1—3%) did not affect the color, aroma, taste, and clarity of the mouthwash. An acute toxicity test on mice model confirmed that the cocoa bean-based mouthwash was safe.